The Synthesis and Co(II), Cu(II), Ni(II), and UO2(VI) Complexes of a New Amino Containing 1,3-Dioxolane - Sekerci, Memet (Maik Nauka/Interperiodica/Springer, 1999)
1,2-O-iso-butylidene-4-aza-7-aminoheptane (L) has been synthesized starting from 1-chloro-2,3-O-iso-butylidenepropane, which has been prepared from the epichlorohydrine and methyl ethyl ketone. Then the complexes of this ligand with Ni(II), Co(II), Cu(II) and UO(2)(VI) salts were prepared. The structure of the ligand in its complexes is proposed according to the (1)H and (13)C NMR, IR, elemental analysis, and magnetic susceptibility measurements, thermogravimetric analysis, and differential thermal analysis.